Irradiation effects in compact binaries - Beer, M; Podsiadlowski, P (2002)
Irradiation of the secondaries in close binary systems affects their appearance and can drastically change their internal structure and hence long-term evolution.. In this paper we review the main effects of external irradiation in close binaries with compact primaries, such as the distortion of the shape of the secondary and the conditions for the occurrence of outer critical configurations; and apply these to normal Xray binaries,, including systems such as HZ Her/Her X-1, Vela X-1 and black-hole binaries during outburst (e.g. Nova Sco). Particular emphasis will be given to the role of circulation driven by the external heating and the radiative surface stress: We have developed a three-dimensional fluid dynamics code for modelling these effects: We present initial results of self-consistent calculations for the circulation in irradiated systems and show how the inclusion of these effects is vital to the understanding and interpretation of any system where external irradiation of the secondary is. significant.